Ni(II) complex containing a thiosemicarbazone ligand: synthesis, spectroscopy, single-crystal X-ray crystallographic and conductivity studies - M. Osman, Uwaisulqarni; Silvarajoo, Sharmili; Kamarudin, Khadijah H.; Mohamed Tahir, Mohamed Ibrahim; Kwong, Huey Chong (Elsevier, 2021)
In this study, 4-(diphenylamino)benzaldehyde-4-(2-fluorophenyl)thiosemicarbazone (LH) ligand was synthesized from the reaction of 4-diphenylaminobenzaldehyde and 2-fluorophenyl thiosemicarbazide. The NiL2 complex containing LH ligand were synthesized and characterized using elemental analysis, infrared spectroscopy, magnetic susceptibility, molar conductivity and UV-Vis spectroscopy. X-ray structure was determined for both the LH ligand and the NiL2 complex. LH ligand was also characterised via 1H NMR and 13C NMR spectroscopy. FTIR data determined the coordination mode of the ligand with Ni(II) metal ion. The FTIR spectra shows that the LH ligand behave as mononegative bidentate through azomethine (N=C) and (C-S) groups with Ni(II) metal ion. The electronic spectra and magnetic measurements agreed well with a square planar geometry for NiL2 complex with the value of 0.00 B.M. Further confirmation of NiL2 complex was determined through single X-ray Crystallography which indicated a distorted square planar geometry which the angles deviated from 90° with a maximum value of 7°. In addition, the structure of LH ligand presented a thione form and the molecule has crystallized in triclinic crystal system with Pī space group. Conductivity studies of polymer electrolyte (PE) films composed of carboxymethyl cellulose (CMC) polymer, propylene carbonate as a plasticizer and LH/NiL2 compound as a dopant were prepared by a solution casting technique. The conductivity of the prepared PE films was studied using Electrochemical Impedance Spectroscopy (EIS). The conductivity was observed for LH ligand and NiL2 complex at 3.73 × 10−9 Scm−1 and 9.81 Scm−1, respectively.